Failure to detect Plasmodium vivax in West and Central Africa by PCR species typing - Culleton, Richard L. (2021)
Background. Plasmodium vivax is estimated to affect 75 million people annually. It is reportedly absent, however, from west and central Africa due to the high prevalence of the Duffy negative phenotype in the indigenous populations. Despite this, non-African travellers consistently return to their own countries with P. vivax malaria after visiting this region. An attempt was made, therefore, to detect the presence of P. vivax parasites in blood samples collected from the indigenous populations of west and central Africa. Methods. Parasite species typing (for all four human malaria parasites) was carried out by PCR on 2,588 blood samples collected from individuals from nine African malaria-endemic countries. Results. Most infections (98.5%) were Plasmodium falciparum, Plasmodium malariae was identified in 8.5% of all infections, and Plasmodium ovale in 3.9%. The prevalence of both parasites varied greatly by country. Only one case of P. vivax was detected from Sao Tome, an island off the west coast of Africa, confirming the scarcity of this parasite in Africa. Conclusion. The prevalence of P. vivax in local populations in sub-Saharan Africa is very low, despite the frequent identification of this parasite in non-African travellers.